DETECTION OF CARBAPENEMASE PRODUCTION IN KLEBSIELLA PNEUMONIAE IN A TERTIARY CARE CENTRE - ABIRAMASUNDARI VK; UMA SEKAR; SHANTHI.M; ARUNAGIRI .K (International Journal of Pharma and Bio Sciences, 2015)
The study was done as a laboratory based study to detect the carbapenemase production in Klebsiella pneumoniae in a tertiary care hospital. A total of 150 clinically significant consecutive isolates of Klebsiella pneumoniae isolated between October 2012 and March 2013 were included in the study. Isolates from outpatients and from urine samples were excluded. The isolates were from blood (50), respiratory secretions (21) and exudates (79). Antibiotic Susceptibility testing to various drugs was performed by disc diffusion method. Carbapenemase production was screened by Modified Hodge Test (MHT) and Klebsiella pneumoniae carbapenemase(KPC) & Metalobetalactamase(MBL) production by inhibitor potentiated disc diffusion tests with Boronic acid and Ethylene Diamine TetraAcetic acid(EDTA) respectively. The isolates were subjected to Polymerase Chain Reaction (PCR) for the detection of blaNDM, blaVIM, blaIMP, blaOXA-48 blaOXA-181 & blaKPC .Out of 150 isolates, 58(39%) exhibited carbapenem resistance. MHT was positive in 49(32.6%) isolates. Among the 49 MHT positive isolates 30 carried MBL genes. Among the 42 MBL screening was positive isolates 37 carried MBL genes. Overall, blaNDM-1, blaVIM & blaIMP genes were detected in 34, 1 & 2 isolates respectively. MIC50 to imipenem was 0.125µg/ml. BlaKPC , blaOXA-48 , blaOXA-181 were not detected. BlaNDM-1 is the main mediator of carbapenem resistance in Klebsiella pneumoniae followed by blaVIM & blaIMP. Carbapenemase production (63.7%) is the most important reason for carbapenem resistance in carbapenem resistant Klebsiella pneumoniae. PCR remains the gold standard for the detection of carbapenemase production.